A The Use of ChatGPT as an English Learning Tool in an Expository and Analytical Writing Class - Aldebarant, Nabil (Faculty of Letters, Universitas Dr. Soetomo, Surabaya, Indonesia, 2025)
This study explores the use of ChatGPT as an English learning tool in an Expository and Analytical Writing class, focusing on students’ usage patterns and the challenges they encountered. A qualitative research design was employed, incorporating classroom observations and semi-structured interviews with 12 English Education students selected through stratified random sampling. Thematic analysis was used to analyze the data. Results indicate that students engaged with ChatGPT during all stages of the writing process except publishing, with particular emphasis on revising, editing, and proofreading. They used ChatGPT to request examples tailored to their writing needs and incorporated selected content into their drafts. While ChatGPT provided valuable support in specific areas of writing, students faced difficulties in crafting effective prompts. The findings suggest that ChatGPT can enhance writing development, but its effectiveness relies on students’ critical engagement and AI literacy to maintain originality and uphold academic integrity.